Icons in Motion: Sacred Aura and Religious Identity in Late Tsarist Russia - Chulos, Chris (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2012)
Throughout Russian Orthodox history the icon has been an important part of the visual and emotional experience of the faithful. Icons that exhibited wondrous powers inspired pilgrimages to their shrines and requests for temporary visitations to local communities hoping that this mobile sacred aura would protect against epidemics or crop failure. As Russia’s autocracy began the long process of modernization in the 1860s and 1870s, loans of wondrous icons became increasingly commonplace as newly literate peasants read about these sacred images in the emerging religious and secular press. Faced with the untested medical and agricultural practices that were being brought to the countryside by educated outsiders, peasant believers supplemented these new techniques with processions honoring wondrous icons. In this way wondrous icons served as important bridges between traditional and modern life as they provided spiritual, physical, and psychological comfort to believers in an uncertain and changing world. For communities whose visitation requests were denied and for believers who wanted their own personal reminder of sacred aura, mass icon reproduction filled this need as millions of copies were manufactured and distributed for free or at negligible cost. The rise in requests for icon visitations and the proliferation of cheaply produced sacred images troubled Church authorities who, facing growing criticism from secular and revolutionary activists and the new religious toleration law of 1905, struggled to bring these popular forms of folk piety within the institutional and bureaucratic structure of Orthodoxy without dampening religious fervor. As spiritual essence emanated from shrines to local communities of believers through visitations and reproductions believers were reminded of the fundamental cultural fragments that bound them together as members of the same faith and as inheritors and creators of modern Orthodox experience as Russia became increasingly modern, secular, and revolutionary.